Communication with the patient’s family - Mukharovska Інна; Abdrjahimova Ціра; Kleban Катерина; Kalachov Олексій (Psychosomatic Medicine and General Practice, 2019)
The disease affects not only the patient himself but also his close environment, which is especially pronounced in situations of chronic and progressive pathology, which significantly changes the physical and mental health of the patient. The article discusses the basic prerequisites for the formation of psychological adaptation states in the family with patients, identifies factors that cause changes in family functioning, patterns of behaviour during the disease, general principles of communication of the doctor with the family and typical difficult situations of interaction.